Virtual Simulation of Hostile Environments for Space Industry: From Space Missions to Territory Monitoring - Luca, Piovano; Valter, Basso; Lorenzo, Rocci; Mauro, Pasquinelli; Christian, Bar; Manuela, Marello; Carlo, Vizzi; Maurizio, Lucenteforte; Michela, Brunello; Filippo, Racca; Massimo, Rabaioli; Eleonora, Menduni; et al. (IntechOpen, 2012)
None